Commodity price volatility and world market integration since 1700 - Jacks, D; O'Rourke, K; Williamson, J (MIT Press, 2011)
Poor countries are more volatile than rich countries, and this volatility impedes their growth. Furthermore, commodity prices are a key source of that volatility. This paper explores price volatility since 1700 to offer three stylized facts: commodity price volatility has not increased over time, commodities have always shown greater price volatility than manufactures, and world market integration breeds less commodity price volatility. Thus, economic isolation is associated with much greater commodity price volatility, while world market integration is associated with less.